Ethical AI Deployment: Balancing Innovation with Responsibility in Pre- Generative AI Systems - Vangala, Vidyasagar (The Eastasouth Journal of Information System and Computer Science, 2024)
With each advance in generative AI technology by virtue of growing innovation, the proportion to be adhered to between responsibility and innovation grows ever more vital. This article discusses the implications of embracing pre-generative AI systems on their ethical concerns and emphasizes the need for urgency in responsibility as part of a realistic usage scenario. The essay presents the ethics of the unexpected surge of the generative AI tools due to concerns of bias, transparency, accountability, and confidentiality. Using the current paradigms of the ethics of AI, the essay creates guiding principles such as fairness, non-maleficence, and user autonomy, and touches on mechanisms for mitigating the likelihood of unwanted consequences. Balancing theory and practice, the book gives developers, organizations, and policymakers advice on how to prepare for an AI system that maximizes ethical use without undermining innovation. Last but not least, it calls for a balance approach that balances technology development and the good of society and dares the stakeholders to embrace constructive and collaborative action in the development of the future of AI deployment.